The Impact of Inquiry-Based Learning on Students' Critical Thinking in Biology Education Programs within Open and Distance Learning Systems - Sapriati, Amalia; Rahayu, Ucu; Sausan, Inas; Sekarwinahyu, Mestika; Anam, Rif'at Shafwatul (Universitas Negeri Semarang, 2024)
This study examines the impact of Inquiry-Based Learning (IBL) on enhancing critical thinking skills in an open and distance learning (ODL) environment, focusing on a biology education program. The research employed a pre-experimental one-group posttest-only design with 35 students participating in online sessions. These sessions involved formulating questions, designing experiments, conducting observations, and analyzing data. Quantitative analysis using percentages, means, standard deviations, and regression revealed that over 75% of students achieved very good performance in key areas like formulating hypotheses and designing experiments. The regression analysis confirmed that IBL significantly affected critical thinking skills (R² = 0.849; p = 0.05). The study concludes that a systematic learning design that encourages active learning and provides continuous feedback is crucial for developing critical thinking skills in ODL settings. These findings provide insights for curriculum developers and educators to optimize IBL implementation, thereby enhancing educational outcomes and fostering independent learning in distance education environments. Further research is suggested to refine this approach and ensure deeper understanding and application of scientific principles.